Ecuación de predicción de la relación diámetro – altura comercial de los arboles Tachigali poeppigiana Tul. según tipo de muestra en bosque natural Puerto Almendra, Loreto, Perú – 2025 - Torres Huaman, Rudiar Alfonso (2025)
The aim of this study was to develop a prediction equation relating diameter to commercial height of Tachigali poeppigiana Tul., known as “tangarana blanca,” according to sampling type in a natural forest in Puerto Almendra, Loreto, Peru, during 2025. The variables considered were diameter at breast height (DBH) and commercial height of trees with DBH ≥ 10 cm. Four sampling types were applied: Sample 1 included 30 individuals distributed into diameter classes with a 4 cm range; Sample 2 also included 30 individuals, with diameter classes of 10 cm; Sample 3 consisted of 30 individuals distributed in 13 cm diameter classes; and Sample 4 included 30 individuals without establishing diameter classes. The results indicate that in the diameter-commercial height relationship of Tachigali poeppigiana Tul. “tangarana blanca” trees in natural forest, the cubic allometric model presented the best fit in the 4 samples; with relationship grades ranging from good to excellent for samples with diameter classes and for samples with no diameter classes; the coefficient of determination determined a maximum of 99,7% of common variations between diameter and marketable height. The prediction equation selected for the diameter-marketable height relationship was: Y = 11.431 + (-0.183 x t) + (0.007 x t2) + (0.00006998 x t3).